2013
DOI: 10.1002/glia.22564
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cells promote corticospinal axonal outgrowth by a L1 CAM‐dependent mechanism

Abstract: Olfactory ensheathing cells (OECs) support the ability of the olfactory neuraxis to continually retarget within the mature central nervous system. This has led many groups to transplant OECS into the lesioned rodent spinal cord (SCd) in vivo, with variable degrees of anatomical, physiological, and behavioral success. Some of the most conflicting results in OEC transplantation have come from the corticospinal tract (CST) which has shown a relatively poor regeneration response. Although spinal neurite sprouting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Studies in animals isolating OECs from the OB proved that OECs can promote axonal outgrowth (Witheford et al, 2013) and benefit in several animal models of CNS traumatic injuries . We have previously demonstrated that OEC-conditioned medium can induce NSCs differentiated into neurons (Duan et al, 2011).…”
Section: Oecs: Great Potential For Sci Repairmentioning
confidence: 98%
“…Studies in animals isolating OECs from the OB proved that OECs can promote axonal outgrowth (Witheford et al, 2013) and benefit in several animal models of CNS traumatic injuries . We have previously demonstrated that OEC-conditioned medium can induce NSCs differentiated into neurons (Duan et al, 2011).…”
Section: Oecs: Great Potential For Sci Repairmentioning
confidence: 98%
“…The source of cells with regenerative potential should be discussed before the choice for particular therapy (classification based on the source of those cells is shown in Figure 2). This review is focused on therapies applying olfactory ensheathing cells, which are proved to act as stimulating axonal growth factors [14] and mesoderm derived mesenchymal stem cells (mainly derived from bone marrow) and their implantation in patients with SCI which are believed to occur through regulation of the immune system, leading to decreased cell death [15]. …”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] NCAM1, which is a major component of OEC-induced corticospinal axon elongation, plays a key role in OEC migration. 28,29) The RT-PCR findings indicate that ginsenoside Rg1 increased the expression of MMP-2, MMP-9, and NCAM1 genes, which stimulate ginsenoside Rg1 in enhancing the migration characteristic of OECs. Thus, these current findings confirm our hypothesis that ginsenoside Rg1 promotes OEC migration and facilitates the repair of SCI via the inhibition of scar formation.…”
Section: Discussionmentioning
confidence: 98%